Re-evaluating Occupational Heat Stress in a Changing Climate - Spector, June T. (Ann Occup Hyg, 2014)
The potential consequences of occupational heat stress in a changing climate on workers, workplaces, and global economies are substantial. Occupational heat stress risk is projected to become particularly high in middle- and low-income tropical and subtropical regions, where optimal controls may not be readily available. This commentary presents occupational heat stress in the context of climate change, reviews its impacts, and reflects on implications for heat stress assessment and control. Future efforts should address limitations of existing heat stress assessment methods and generate economical, practical, and universal approaches that can incorporate data of varying levels of detail, depending on resources. Validation of these methods should be performed in a wider variety of environments, and data should be collected and analyzed centrally for both local and large-scale hazard assessments and to guide heat stress adaptation planning. Heat stress standards should take into account variability in worker acclimatization, other vulnerabilities, and workplace resources. The effectiveness of controls that are feasible and acceptable should be evaluated. Exposure scientists are needed, in collaboration with experts in other areas, to effectively prevent and control occupational heat stress in a changing climate.